Thermal oxidation of AIAs and the possibility of confinement in an optical device - Agra, Francisco A.
The wet oxidation of AIAs layers and its ability to confine current in an optical device was investigated in this study. Two samples were grown by molecular beam epitaxy. One consists of a thick (300 nm) AIAs layer in GaAs while the other contains thin (60 nm) AIAs layers in a p-i-n device employing a vertical cavity surface emitting laser structure. Fresh edges of AIAs layers embedded within the samples were prepared either by simple cleaving or by lithographically patterning and etching into 225 um diameter mesas. Sections cut from both samples were heated in a modified wet oxidation furnace to oxidize the AIAs layers at different time and temperature values. Oxidation proceeds laterally starting from the edge. The extent of oxidation, defined as the length of oxide formed starting from the edge up to the AIAs/oxide interface, was compared for all samples.